Business entrepreneurship in nursing care facilities in Brazil: an ecological study - Matheus Moraes Silva; Jouhanna do Carmo Menegaz; Glenda Roberta Oliveira Naiff Ferreira; Josele de Jesus Quaresma Trindade Costa; Maria Eduarda Libório Martins; Allison Squires (Revista Latino-Americana de Enfermagem, 2025)
Objective: to characterize and describe the spatial and temporal distribution of nursing care establishments in Brazil according to the National Registry of Health Establishments. Method: ecological study, using secondary data from the National Register of Health Establishments, aggregated by year, state and region. The variables extracted were: year of registration, gender of the nurse manager or administrator, number of nurses per establishment, type of establishment, main activity, level of care, legal nature and agreement. Descriptive statistics and temporal analysis were carried out using the Jointpoint program. Results: between 2003 and 2023, 340 nursing establishments were found with active registrations. The South and Southeast concentrated most of the establishments. There was a predominance of practices, specialized clinics and home care services. The temporal analysis indicated that between 2003 and 2021, there was an annual growth of 30.07% (p= 0.00). Considering the total period (2003-2023), there was an annual growth of 25.01%, indicating an upward trend in businesses over the years. Conclusion: formalization and registration reflect the professionalization of nursing management. There has been an increase in registrations following the publication of resolutions by the Federal Nursing Council that support autonomous and/or liberal practice.